Isolasi dan Identifikasi Bakteri Gram Negatif pada Kloaka Ayam Layer di Mamben Daya, Lombok Timur - Ayu Afriani; Candra Dwi Atma; Alifianita Anake Yansri; Katty Hendriana Priscilia Riwu (Biocaster : Jurnal Kajian Biologi, 2026)
Gram-negative bacteria in layer chickens have the potential to be a source of infection and a reservoir of pathogens that impact animal and human health, as well as the safety of poultry-derived food. The presence of these bacteria in the cloaca reflects the level of microbial contamination in the farm environment and can be an indicator of low barn sanitation and biosecurity. This study aimed to isolate and identify gram-negative bacteria in the cloaca of layer chickens in Mamben Daya Village, Wanasaba District, East Lombok Regency. The study used a descriptive laboratory design with 35 cloacal swab samples taken randomly from smallholder farms. Bacterial isolation was carried out through a pre-enrichment stage using Buffered Peptone Water (BPW), followed by enrichment with Selenite F Broth, and cultivation on selective Xylose Lysine Deoxycholate (XLD) media. Identification was carried out through gram staining and biochemical tests including sugar tests, Sulfide Indole Motility (SIM), Triple Sugar Iron Agar (TSIA), and Simmons Citrate Agar (SCA). The results showed that 34 of 35 samples (97.14%) were positive for gram-negative bacilli. Biochemical tests identified bacteria from the Enterobacteriaceae family, namely Escherichia coli, Escherichia spp., Citrobacter spp. (Citrobacter freundii and Citrobacter diversus), and Klebsiella oxytoca, with Escherichia coli as the dominant isolate. The dominance of Escherichia coli indicates a high risk of contamination of the farm environment and poultry-derived food products, which could impact public health. This finding underscores the importance of implementing biosecurity, barn sanitation, and regular microbiological monitoring to support livestock health and food safety.